Evaluation of GeneXpert MTB/RIF assay in diagnosis of extrapulmonary tuberculosis and rifampicin resistance - Dr. Jagadevi; Dr. Sumanta A; Dr. Shubha D S.; Dr. Sudhindra K.S.; Dr. Basavaraj Sangolli (Tropical Journal of Pathology and Microbiology, 2018)
Background: The prevalence of tuberculosis is still on the rise particularly extrapulmonary cases. There is an urgent need for rapid diagnosis of these cases for prompt initiation of treatment. Aim: To evaluate the role of GeneXpert MTB/RIF Assay in the diagnosis of clinically suspected extrapulmonary tuberculosis (EPTB) and to detect rifampicin resistance in these cases. Materials and methods: A total of 241 samples from April 2016 to July 2018, from all clinically suspected EPTB patients with support of either laboratory or radiological evidence were included in study. 132 pleural fluid, 59 lymph node aspirate, 21 CSF, 17 pus, 9 ascitic fluid and 3 synovial fluid samples were screened for presence of acid fast bacilli (AFB) by conventional Zeihl-Neelsen (ZN) technique. The same samples were also used for testing by GeneXpert MTB/RIF Assay. Results: Out of 241 EPTB samples tested, none were positive for AFB by ZN staining. Overall 9.54 % (23 out of 241) samples were positive for MTB by GeneXpert with a positivity rate of 23.80%, 13.55%, 11.76% & 6.06% respectively for CSF, lymph node aspirate, pus and pleural fluid. MTB was not detected in any of ascitic fluid & synovial fluid samples. Of the 23 MTB positive samples detected by GeneXpert, all were sensitive to rifampicin. Conclusions: GeneXpert was found to be simple, effective and useful diagnostic method for detection of EPTB due to its rapidity & simultaneous detection of rifampicin resistance, thus reducing the time taken for initiation of treatment.